In vitro study of the tocolytic effect of oroxylin A from Scutellaria baicalensis root - Yang Ling-Ling; Hsu Chun-Sen; Shih Huey-Chuan (Journal of Biomedical Science, 2009)
Abstract Scutellariae Radix is one of the well-known tocolytic Chinese herbs. Oroxylin A is isolated from the root of Scutellaria baicalensis. The main syndrome of preterm birth is caused by uterus contractions from excitatory factors. Administration of tocolytic agents is a strategy to prevent the occurrence of preterm births. The aim of this study was to investigate the effects of oroxylin A on contractions of uterine strips isolated from non-pregnant female Wistar rats (250~350 g). Contractions of the uterus were induced with acetylcholine (Ach) (1 μM), PGF2α (0.1 μM), oxytocin (10-3 U/ml), KCl (56.3 mM), tetraethylammonium (TEA; 1 and 10 mM), 4-aminopyridine (4-AP; 5 mM), glipizide (30 μM), a nitric oxide synthase (NOS) inhibitor (LNNA; 10-3M), a β-receptor blocker (propranolol; 10 μM), and a cyclooxygenase inhibitor (indomethacin; 60 μM). The inhibitory effects of the amplitude and frequency of spontaneous contractions by oroxylin A were antagonized with Ach (IC50 22.85 μM), PGF2α (IC5027.28 μM), oxytocin (IC50 12.34 μM), TEA; 1 and 10 mM (IC50 52.73 and 76.43 μM), 4-AP (IC50 67.16 μM), and glipizide (IC5027.53 μM), but oroxylin A was not influenced by Ca2+-free medium, LNNA, propranolol, or indomethacin. Otherwise, oroxylin A-mediated relaxation of the rat uterus might occur through opening of uterine calcium-dependent potassium channels or adenosine triphosphate potassium channel activation. This suggests that oroxylin A is the tocolytic principle constituent of Scutellariae Radix, and oroxylin A may provide a lead compound for new tocolytic drug development in the future.